CONCEPTUAL APPROACHES TO MARKET REFORMING OF MEDICAL INSURANCE OF THE REPUBLIC OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2022)
This article discusses the problems and main directions for improving the insurance market of the Republic of Uzbekistan. Today, the insurance market is one of the priorities in the country's economy. Uzbekistan pays attention to the development of medical insurance, which once again underlines the importance of developing the insurance market. The insurance industry is undergoing significant transformations aimed at creating a new financial and economic system with multiple growth points. Therefore, the state develops not only a strategy for its socio-economic development, but also key strategic directions, which include macroeconomic processes for the development of insurance, which play a crucial role in the system of the domestic and world economy.